Analisis Kemampuan Pemecahan Masalah Mahasiswa dalam Menyelesaikan Soal Non Rutin pada Materi Limit - Natumnea, Rina Ivani Natalia; Mumu, Jeinne; Wyrasti, Andi Fajeriani; Irnandi, Irfan; Sampouw, Falenthino (Jurnal Pendidikan Matematika : Judika Education, 2026)
This research aims to analyze college students’ problem-solving abilities in solving non-routine promblems on the topic of limits. The type of research employed is descriptive qualitative. The research subjects were 15 mathematics students at Universitas Papua. From the total subjects, 4 students were selected using a purposive sampling technique as focus subjects for in depth interviews, consisting of two subjects from the moderate category and two subjects from the low category. Data analysis was conducted based on Polya’s problem-solving stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The results indicated that the majority of students were in the low ability category (12 students) and the remaining were in the moderate category (3 students0. Moderate category subjects were able to understand the problem well and write down fairly systematic resolution steps, but lacked precision in final execution. Meanwhile, low category subjects showed effort to resolve the problems but faced major obstacles during the stages of devising and carrying out plans due to weak understanding of prerequisite concepts, and all subjects tended to neglect the looking-back stage. In conclusion, students’ problem-solving ability in solving non-routine limit problems is dominated by the low category. Learning approaches that habituate students to solving non-routine tasks and strengthening metacognitive aspects in re-evaluating their work are highly required.   Keywords: Problem-Solving Ability, Non-Routine Problems, Limit, Polya